2007
DOI: 10.1029/2006jd007241
|View full text |Cite
|
Sign up to set email alerts
|

Optimal estimation of the soil uptake rate of molecular hydrogen from the Advanced Global Atmospheric Gases Experiment and other measurements

Abstract: Hydrogen (H2), a proposed clean energy alternative, warrants detailed investigation of its global budget and future environmental impacts. The magnitudes and seasonal cycles of the major (presumably microbial) soil sink of hydrogen have been estimated from high‐frequency in situ AGAGE H2 observations and also from more geographically extensive but low‐frequency flask measurements from CSIRO and NOAA‐GMD using the Kalman filter in a two‐dimensional (2‐D) global transport model. Hydrogen mole fractions exhibit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 43 publications
7
103
1
1
Order By: Relevance
“…For Bousquet et al (2011), we have indicated the standard deviation of the sensitivity inversions based on the reference scenario (external errors). The errors in Xiao et al (2007) include model uncertainties, absolute calibration error and errors in the assumed fossil fuel source strength. For each region, we indicate the relative proportion of each regional source or sink in comparison with the global source or sink.…”
Section: H 2 Budgetmentioning
confidence: 99%
See 3 more Smart Citations
“…For Bousquet et al (2011), we have indicated the standard deviation of the sensitivity inversions based on the reference scenario (external errors). The errors in Xiao et al (2007) include model uncertainties, absolute calibration error and errors in the assumed fossil fuel source strength. For each region, we indicate the relative proportion of each regional source or sink in comparison with the global source or sink.…”
Section: H 2 Budgetmentioning
confidence: 99%
“…The global estimations for each term as given in Xiao et al (2007) and Bousquet et al (2011) are added in Table 4. Estimating the uncertainties of the posterior fluxes can be done using the MonteCarlo approach of Chevallier et al (2007).…”
Section: H 2 Budgetmentioning
confidence: 99%
See 2 more Smart Citations
“…The two major atmospheric H 2 sources are photochemical production from methane and non-methane hydrocarbons and combustion of fossil fuels and biomass (Novelli et al, 1999). The major H 2 sinks are soil consumption, representing about 81 ± 8 % of the total sink, and oxidation by OH being about 17 ± 3 % based on a global inversion of sparse atmospheric H 2 measurements (Xiao et al, 2007). The major sources and sinks are nearly balanced so atmospheric H 2 concentrations are stable.…”
Section: Introductionmentioning
confidence: 99%